2018
DOI: 10.2196/medinform.9907
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modeling of 30-Day Emergency Hospital Transport of Patients Using a Personal Emergency Response System: Prognostic Retrospective Study

Abstract: BackgroundTelehealth programs have been successful in reducing 30-day readmissions and emergency department visits. However, such programs often focus on the costliest patients with multiple morbidities and last for only 30 to 60 days postdischarge. Inexpensive monitoring of elderly patients via a personal emergency response system (PERS) to identify those at high risk for emergency hospital transport could be used to target interventions and prevent avoidable use of costly readmissions and emergency departmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The service is partially privately paid for by participants and not covered by their health insurance. 20 To limit sampling bias, all subscribers to the service between January 2012 and June 2014 who subscribed for at least 3 months were included in the eligible cohort. We selected a convenience sample that included all self-reported PD participants (n = 2063).…”
Section: Methodology Study Design and Participantsmentioning
confidence: 99%
“…The service is partially privately paid for by participants and not covered by their health insurance. 20 To limit sampling bias, all subscribers to the service between January 2012 and June 2014 who subscribed for at least 3 months were included in the eligible cohort. We selected a convenience sample that included all self-reported PD participants (n = 2063).…”
Section: Methodology Study Design and Participantsmentioning
confidence: 99%
“…During the study, the participants’ risk will be assessed by a predictive model of hospital transport in the next 30 days. This predictive risk model was developed on a retrospective data set of more than 8000 deceased German PERS subscribers using a methodology similar as described in [ 7 ], which is used by the Philips CareSage predictive analytics engine in the United States. The predictive model achieved an area under the receiver operator characteristic curve of 0.75.…”
Section: Methodsmentioning
confidence: 99%
“…The main benefit of a PERS service is the reassurance that help will always be available in case of an emergency, such as a fall or respiratory issues. Previous studies in the United States (US) [ 7 , 8 ] have shown that PERS data can be used to develop prediction models of decline in patient status. Such models thus provide early warning signs of impending emergencies and can be used by case managers to provide timely intervention [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In [21], a predictive model was developed to predict the risk of emergency hospital transport of elderly patients within the next 30 days. Based on a dataset of ≈ 290 000 patients and 128 features (of which approximately half were binary) and a binary output variable (transport/no transport), a predictive model was constructed using extreme gradient boosted trees.…”
Section: Applicationmentioning
confidence: 99%
“…Because the dataset is highly skewed towards no transport required (≈ 98% of cases), we present the accuracy of the method using precision and recall for three thresholds (90th, 95th and 99th percentile). We refer to [21] for the details.…”
Section: Applicationmentioning
confidence: 99%